A Faculdade de Educação nos Anos 60: releitura da "idade de ouro"The College School of Education in the Sixties: a new view on the "golden age" (PerCursos, 2007)
O artigo procura fazer uma releitura crítica e contextualizada da Faculdade de Educação da Universidade do Estado de Santa Catarina (UDESC) no momento da sua fundação – 1963 – e de sua atuação institucional na década de 60. Analisa o Centro de Estudos e Pesquisas Educacionais (CEPE) e o Curso de Pedagogia, órgãos da Faculdade de Educação, sublinhando a sua estreita vinculação com a política educacional do governo do Estado de Santa Catarina, explicitada no Plano de Metas do Governo, o PLAMEG. Palavras-chave: Faculdade de Educação; pedagogia; pesquisa educacional.Abstract: The article aims at a critical and contextualized reevaluation of the School of Education at Santa Catarina State University (UDESC) in the moment of its foundation – 1963 -, and its institutional action in the decade of 1960. It analizes the Educational Studies and Researches Center (CEPE) and the Pedagogy Course, both belonging to the Education School, underlining their close link with the educational politics of Santa Catarina State government, clearly expressed in the Government Goals Plan – PLAMEG.Key Word: College School of Education; pedagogy; educational research.